A THE RELATIONSHIP BETWEEN ANTIHYPERTENSION DRINKING COMPLIANCE AND QUALITY OF LIFE IN HYPERTENSION PATIENTS AT HARAPAN KELUARGA HOSPITAL (RADJAK HOSPITALS GROUP) - Rino Cahyono Simbolon (Jurnal Nurse, 2024)
Background : Hypertension is a disease that is not contagious but becomes a hidden killer or what is called a "silent killer". Hypertensive patients who do not take medication therapy for a long time will cause complications, if these conditions cannot be treated, they will cause discomfort and will affect the quality of life of hypertensive patients. Objective: To determine the relationship between medication adherence and quality of life in hypertensive patients at Harapan Keluarga Jababeka Hospital. Methods: This study used a cross sectional study design. The study respondents consisted of 74 hypertensive patients at Harapan Keluarga Jababeka Hospital. Retrieval of data using purposive sampling technique. Retrieval of data using a questionnaire instrument. The data analysis technique used is the Pearson's correlation test. Results: This study stated that for medication adherence in patients stated 84% had moderate medication adherence category with a quality of life level of 64% had a high quality of life category. Pearson's correlation analysis shows that the value of r = 0.257 and p = 0.027 (<0.05) indicates that the relationship that occurs is low. Conclusions and suggestions: From the results of the analysis above, it can be concluded that there is a relationship between medication adherence to quality of life. From this research it is hoped that it can improve the quality of life with adherence to taking medication.